Anatomic Variation of the Lateral Sinus in Patients With Idiopathic Intracranial Hypertension: Delineation With Black-Blood Contrast-Enhanced MRI - Tian, Yu; Zhang, Zhe; Jing, Jing; Dong, Kehui; Mo, Dapeng; Wang, Yilong (Frontiers in Neurology, 2021)
Objectives: The purpose of this study was to describe the peculiar anatomic variations in the lateral sinus and analyze the patterns of cerebrospinal fluid (CSF) drainage by using high-resolution (HR) black-blood (BB) contrast-enhanced magnetic resonance imaging (MRI) in patients with idiopathic intracranial hypertension (IIH). Methods: Total 33 IIH patients who were found cerebral venous sinus stenosis (CVSS) by MR venography (MRV) were enrolled in this study. HR-BB contrast-enhanced MRI was used to assess the features of anatomical variations in transverse sinus and sigmoid sinus. The development of bilateral sinuses was firstly evaluated, including unilateral hypoplasia with contralateral dominance or bilateral balanced development. Then, four kinds of anatomical variations were eventually recorded, including circumscribed stenosis, arachnoid granulation (AG), fibrous septum (FS), and brain herniation (BH) into dural venous sinus (DVS). Results: Bilateral venous drainage dysfunction was found in 30(90.9%) patients, whereas only 3(9.1%) patients presented unilateral venous drainage dysfunction. There was no difference in clinical symptoms between the two groups. The most common case is hypoplasia in unilateral sinus combined with anatomic variation in the contralateral dominant transverse sinus such as AG and BH into DVS. Total of 52 anatomic variations were finally found in bilateral sinuses in 33 enrolled patients, including 19(36.5%)AGs, 12(23.1%)FS, 7(13.5%) BH into DVS and 14(26.9%) circumscribed stenoses. Moreover, 41(62.1%) lateral sinuses showed enhancement in T1-weight-enhanced MRI. Conclusions: Patients with CVSS almost had CSF outflow disorders, whatever bilateral equalization or unilateral hypoplasia with contralateral dominance. Four types of main anatomic variations, including circumscribed stenosis, AG, FS, and BH into DVS, caused venous reflux obstruction by elevating the intracranial press (ICP).